ZOOPLANKTON COMMUNITY STRUCTURE IN THE RAINY SEASON AS A BIOINDICator OF WATER QUALITY IN NAMBERAN TELAGA GUNUNGKIDUL DISTRICT - Nurrahmantyo, Guntang; Sudarsono (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2024)
This research aims to determine: (1) The structure of the zooplankton community in Telaga Namberan, Gunungkidul Regency, (2) The chemical and physical conditions of the waters in Telaga Namberan, Gunungkidul Regency, (3) The relationship between the structure of the zooplankton community and water quality in Telaga Namberan, Regency Gunungkidul. This research is exploratory research with observational research methods. Sampling was carried out at 6 stations 2 times with 3 repetitions. The research results show that the abundance value is 16216.56 - 877388.54 ind/L, meaning it is classified as water with high nutrient levels. The average dominance value of 0.495 means that the community structure is in a stable condition. The average diversity value is 1.098, meaning that the number of individuals of each species is relatively evenly distributed with fairly stable water conditions. The average evenness value is 0.501, meaning it has even species and the community is relatively stable. Frequency of attendanceCyclopssp., Nauplius sp., Notholca sp 1 always appear at all stations because they can adapt and fit to live in the environment.